PANCASILA DALAM KEHIDUPAN MUSLIM DI LINGKUNGAN MASJID AL MANAR MENDUNGAN - Siti Shofiyatun (Institut Islam Mamba'ul 'Ulum Surakarta, 2019)
Pancasila is a guide for the Indonesian people in society, nation and state. Over time, the ideology of the Pancasila began to fade in people's lives; this could be due to the current of globalization. The community began not to pay too much attention to the values in the Pancasila. As one example this can be seen around the Al-Manar mosque which tends to individualism. The existing Pancasila values seem to be marginalized and become a new problem today. Itmakes writer to examine how the people understand the Pancasila in the Al-Manar mosque and how to plant the values of Pancasila and religious teachings in Muslim life in the Al-Manar mosque The purpose of this paper is to be able to provide insight to the community on the importance of planting Pancasila values and teachings. The method used in this study is qualitative descriptive. Data is collected through observation, interviews and documents related to research. The technique used in analyzing is spreading data, retrieving data according to the problem and drawing conclusions. From the results of the study it was found that the majority of the people in the Al-Manar mosque understood the meaning and function of the Pancasila as the state foundation and unifying the Indonesian nation. Pancasila values do not conflict with the values of Islamic teachings. The pattern of understanding of some Muslim communities in the Al-Manar mosque understands Pancasila as its own ideology, and the teachings of Islam as its own ideology.